An overview of Indigenous peoples in Chile and their struggle to revitalise their native languages: the case of Mapudungun (UCL Press, 2022)
Languages are not just sets of words. They are powerful tools essential to carry history, traditions, culture and wisdom. In Latin America, Mapudungun, the native language of Mapuche people - the largest ethnic group in Chile - can be threatened. A substantial linguistic shift has characterised the panorama of native languages of the current territory. However, language and education policies have been insufficient for their preservation. This article analyses Mapudungun from a general historical perspective to define Indigenous communities' experience in the country: insufficient state support for revitalising their languages and decolonising the Chilean national curriculum. An overview of Mapudungun in the last century is provided by explaining relevant linguistic and educational policies. The PEIB (Intercultural Bilingual Education Programme), a linguistic and educational policy in Chile, is considered in depth. It aims to improve the quality and relevance of learning from curricular contextualisation. It also seeks to teach Indigenous children their culture, traditions and languages. However, the lack of support for traditional educators and the decontextualised curriculum have further impoverished their background and increased the gap between native peoples' languages and Chilean society. The article ends with a call to policymakers to recognise the importance of the construction of Chilean identities.